Demonstrating the Use of a Class of Min‐Max Smoothers for D Region Event Detection in Narrow Band VLF Phase. Issue 3 (5th March 2019) - Lotz, S. I.; Clilverd, M.
Abstract: This paper describes the use of a class of nonlinear smoothers for the identification of interesting phenomena in narrow band very low frequency (VLF) transmission phase caused by perturbation events in the D region of the ionosphere. The LULU smoothers, named for their smoothing of upward (L) and downward (U) peaks in a signal, usually used for image processing tasks, are described, and examples are shown where these operators are used to automatically isolate and identify features in the phase of narrow band transmissions received at high and high‐middle latitudes (Antarctica and Marion Island, respectively). Identification of solar flare events, electromagnetic ion cyclotron wave precipitation, and substorm injection events are demonstrated, showing the potential for this technique to be used for space weather monitoring. Key Points: We demonstrate the use of LULU operators for event detection in narrow band VLF signal phase LULU is used to identify solar flares, EMIC wave precipitation events, and substorms from VLF phase We show that events could be isolated without the explicit need for estimating a quiet day curve